The Variation Effect of Electric Current Toward Tensile Strength on Low Carbon Steel Welding with Electrode E7018 - Pratomo, Muhammad Agung; Jasman, Jasman; Erizon, Nelvi; Fernanda, Yolli (Teknomekanik, 2020)
The strength of the welding result is strongly influenced by several factors, one of which is the selection of high current. This study aims to determine the effect of high current of welding on the strength of low carbon steel welding joints. The process of welding the material uses the open V seam connection type. The variations of the high current used were 80 A, 100 A and 130 A. The specimen used was a carbon steel plate with code of 1.0038 with thickness of 8 mm and the electrode used was the E7018 electrode with diameter of 3.2 mm. The strength of the welding results is influenced by arc voltage, amount of current, welding speed, amount of penetration and electric polarity. Determination of the amount of current in metal joints using arc welding affects the work efficiency and welding materials. Based on the research, it was found that welding using high current of 100 ampere produced the highest tensile strength value of all test specimens that were given welding treatment and good penetration results.